Analisis Job Value dan Perancangan Struktur Gaji Baru Pada Perusahaan Pengolahan Semen Instan PT XYZ di Kabupaten Semarang - Nur Ramadhan, Akbar; Tyas Permata Dewi, Aning; Prasetyo Wardhani, Ichsan; Nurul Wulan, Maghfiroh; Hermansyah, Muhamad (Rifa'Institute, 2021)
PT XYZ is a factory engaged in the instant cement or mortarindustry located in Semarang Regency, Central Java, which has beenestablished since 2013. The company is managed by a presidentdirector who supervises 36 contract employees. The compensationsystem used by PT XYZ is to pay a basic salary of Rp. 11,515/hourobtained from the UMR of Semarang Regency divided by 200working hours. The compensation system applies to all positions atPT XYZ except for director and the factors that affect the amount ofbasic salary received depend on the number of hours worked eachmonth. The amount of the director's salary has its own rulesaccording to the agreement of the commissioner. Determination ofcompensation applied in the company is not ideal because it is onlydetermined by working hours without considering other factors.Thus, this study aims to evaluate the compensation system at PTXYZ based on a salary survey, salary mapping, and Eckenrodesystem in order to provide a better description of the compensationsystem for PT XYZ in order to assist the company in improving itsperformance. This study found ten compensable factors thatmatched the work of PT XYZ, which were obtained using the haymethod. The calculation results of the adhered and overlappingmethods are used to classify employee salaries into five grades.